MAIL SERVICE PADA VIRTUAL NETWORKING SYSTEM ( VINES ) - Fachrudin Fachrudin; Ir. Irwan Nirmara, MM (Jurnal Sistem Komputer, 2002)
Mail service is part of the Opti onal Service Virtual Networking System (VINES) Banyan Incorporated which is a system for exchanging information quickly and accurately. The documents can be sent or communicated with the format as the original, so that recipients can use effectively. Messa ge in queue distinguished from each other by the ID of each message. Copies of the same message has a special ID with ten characters the same and are distinguished by the character of the eleventh different. Excess owned Mail Service from Banyan VINES MailÂ  when compared with other systems, among others that can easily get the address or name of someone using a system called StreetTalk.Â